All-optical routing functionalities - Reis, Cláudia Sofia Marcos Machado (2014)
All-optical solutions for switching and routing packet-based traffic are crucial for realizing a truly transparent network. To meet the increasing requirements for higher bandwidth, such optical packet switched networks may require the implementation of digital functions in the physical layer. This scenario stimulated us to research and develop innovative high-speed all-optical storage memories, focusing mainly on bistables whose state switching is triggered by a pulsed clock signal. In clocked devices, a synchronization signal is responsible for controlling the enabling of the bistable. This thesis also presents novel solutions to implement optical logic gates, which are basic building blocks of any processing system and a fundamental element for the development of complex processing functionalities. Most of the proposed schemes developed in this work are based on SOA-MZI structures due to their inherent characteristics such as, high extinction ratio, high operation speed, high integration capability and compactness. We addressed the experimental implementation of an all-optical packet routing scheme, with contention resolution capability, using interconnected SOAMZIs. The impact on the system performance of the reminiscent power of the blocked packets, from the non ideal switching performed by the SOA-MZIs, was also assessed.